Perfluorooctanoate and Perfluorooctanesulfonate plasma concentrations and survival after prostate and bladder cancer in a population-based study. Issue 3 (September 2018) - Roswall, Nina; Larsen, Signe Benzon; Sørensen, Mette; Tjønneland, Anne; Raaschou-Nielsen, Ole
Abstract : Background: Perfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS) are synthetically produced chemicals, which have been linked to cancer in animal studies, whereas the evidence in humans is merely suggestive. We investigated the association between PFOA and PFOS concentrations in plasma samples and mortality in two survivor cohorts of prostate and bladder cancer patients. Methods: We included 688 prostate and 307 bladder cancer cases diagnosed between baseline (1993–97) and July 1, 2006 in the Danish Diet, Cancer and Health cohort. PFOA and PFOS concentrations in plasma samples taken at baseline were measured using high-pressure liquid chromatography. We used Cox proportional hazards models to estimate mortality rate ratios. Results: Between diagnosis and February 1, 2016, 356 prostate and 149 bladder cancer cases died. We found no association between PFOA or PFOS concentrations and survival among prostate cancer cases. This was regardless of prognostic factors. For bladder cancer cases, there was an inverse association between PFOA and PFOS and subsequent mortality. Associations were similar for both overall and bladder cancer-specific mortality. Conclusions: The results of the present study does not suggest an association between PFOA or PFOS concentrations and survival among prostate cancer patients. In contrast, they may be inversely associated with both overall and bladder cancer–specific mortality in bladder cancer patients. However, this finding requires replication in further studies before firm conclusions can be drawn. Abstract : Supplemental Digital Content is available in the text.